EFEKTIVITAS PEMBELAJARAN MATEMATIKA MELALUI PERMAINAN TRADISIONAL PADA MATERI BANGUN DATAR SISWA KELAS IV SD INPRES BONTOMANAI - Ramadhani, Magfirah; Nasrun; Alim Syahri, Andi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of mathematics learning through traditional games of engklek on the material of plane figures of fourth-grade students of SD Inpres Bontomanai. This pre-experimental study with a one-group pretest-posttest design involved 31 students as a total sample. The effectiveness of learning was reviewed from learning outcomes, student and teacher activities, and student responses. The results showed a significant increase in learning outcomes, marked by an average pre-test score of 43.55 increasing to 85.16 in the post-test with an N-Gain of 0.71 in the high category. Student activity was in the active category with an average percentage of 73.71%, teacher activity was in the good category with an average value of 3.17, and student responses to learning through engklek games were classified as very positive with a percentage of 81.8%. Based on these results, it can be concluded that the application of traditional engklek games is effective in learning mathematics on plane figures for fourth-grade students of SD Inpres Bontomanai.